Evolution of Abscisic Acid Signaling Module and Its Perception - Sun, Yufei; Pri-Tal, Oded; Michaeli, Daphna; Mosquna, Assaf (Frontiers in Plant Science, 2020)
We hereby review the perception and responses to the stress hormone abscisic acid (ABA), along the trajectory of 500M years of plant evolution, whose understanding may resolve how plants acquired this signaling pathway essential for the colonization of land. ABA levels rise in response to abiotic stresses, coordinating physiological and metabolic responses, helping plants survive stressful environments. In land plants, ABA signaling cascade leads to growth arrest and large-scale changes in transcript levels, required for coping with environmental stressors. This response is regulated by a PYRABACTIN RESISTANCE 1-like (PYL) - PROTEIN PHOSPHATASE 2C (PP2C) - SNF1-RELATED PROTEIN KINASE 2 (SnRK2) module, that initiates phosphor-activation of transcription factors and ion channels. The enzymatic portions of this module (phosphatase and kinase) are functionally conserved from streptophyte algae to angiosperms, whereas the regulatory component –the PYL receptors, putatively evolved in the common ancestor of Zygnematophyceae and embryophyte as a constitutive, ABA-independent protein, further evolving into a ligand-activated receptor at the embryophyta. This evolutionary process peaked with the appearance of the strictly ABA-dependent subfamily III stress-triggered angiosperms’ dimeric PYL receptors. The emerging picture is that the ancestor of land plants and its predecessors synthesized ABA, as its biosynthetic pathway is conserved between ancestral and current day algae. Despite this ability, it was only the common ancestor of land plants which acquired the hormonal-modulation of PYL activity by ABA. This raises several questions regarding both ABA’s function in ABA-non-responsive organisms, and the evolutionary aspects of the ABA signal transduction pathway.